2004
DOI: 10.1001/archotol.130.9.1100
|View full text |Cite
|
Sign up to set email alerts
|

Aspiration, Weight Loss, and Quality of Life in Head and Neck Cancer Survivors

Abstract: To determine associations between objective assessments (swallowing function and weight change) and subjective quality-of-life (QOL) measures. Design: Observational case series using clinical testing and questionnaires. Setting: University hospital-based tertiary clinical practice. Patients: Convenience sample of 5-year survivors of head and neck cancer (62 nonlaryngectomy survivors were studied). Interventions: Objective testing included examination, weight history, videofluoroscopic swallow studies (VFSS), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
70
4
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(83 citation statements)
references
References 11 publications
7
70
4
2
Order By: Relevance
“…Specifically, significant improvement was found for physical and functional components of performing everyday activities, as reported by Epstein and colleagues 77 who found almost 60% of a heterogenous head and neck cancer population treated with surgery and/or radiotherapy reported no limitations at work or performing household jobs at 6-12 months post-treatment. As in the current study, negative outcomes at 6 months have been reported for the physical and head and neck specific concerns, largely reflecting the ongoing trouble with swallowing, social eating, dry mouth, sticky saliva, and mouth opening in the irradiated population 78,79 . In addition, weight loss of 10% or more in 6 months, as found in the current study, has been associated with increased morbidity such as impaired wound healing, reduced immune function, and increased mortality, and has also been shown to impact on quality of life and functional outcomes [80][81][82][83] .…”
Section: Six Months Post-treatmentsupporting
confidence: 60%
“…Specifically, significant improvement was found for physical and functional components of performing everyday activities, as reported by Epstein and colleagues 77 who found almost 60% of a heterogenous head and neck cancer population treated with surgery and/or radiotherapy reported no limitations at work or performing household jobs at 6-12 months post-treatment. As in the current study, negative outcomes at 6 months have been reported for the physical and head and neck specific concerns, largely reflecting the ongoing trouble with swallowing, social eating, dry mouth, sticky saliva, and mouth opening in the irradiated population 78,79 . In addition, weight loss of 10% or more in 6 months, as found in the current study, has been associated with increased morbidity such as impaired wound healing, reduced immune function, and increased mortality, and has also been shown to impact on quality of life and functional outcomes [80][81][82][83] .…”
Section: Six Months Post-treatmentsupporting
confidence: 60%
“…In addition, poor swallowing function may exert more than a detrimental effect on HRQOL. 33 Unrecognized aspiration following chemoradiation to treat HNC may also contribute to mortality. Aspiration pneumonia may add substantially to the morbidity and mortality associated with HNC treatment, although this long-term adverse effect may not be easily identified as a result of cancer therapy.…”
Section: Commentmentioning
confidence: 99%
“…In this sense, some studies indicate the need for assessing the quality of life of cancer patients for a good understanding of the degree of improvement and/or stabilization, or even worse, obtained with therapeutic procedures (2) . There are studies describing the association of dysphagia with the decline in quality of life during oncological treatment (3)(4)(5)(6)(7) . In head and neck cancer, this association has been studied through the application of symptom-specific quality of life questionnaires (8)(9)(10)(11)(12)(13) , considered effective in assessing the impact of the disease in affected individuals.…”
Section: Introductionmentioning
confidence: 99%